Floral micromorphology of the bird-pollinated carnivorous plant species utricularia menziesii r.br. (lentibulariaceae) - Plachno, Bartosz J.; Stpiczynska, Małgorzata; Swiatek, Piotr; Lambers, Hans; Miranda, Vitor F. O. [UNESP]; Nge, Francis J.; Stolarczyk, Piotr; Cawthray, Gregory R. (Oxford University Press (OUP), 2019)
• Background and Aims Bird pollination is rare among species in the genus Utricularia, and has evolved independently in two lineages of this genus. In Western Australia, the Western Spinebill, Acanthorhynchus superciliosus, visits flowers of Utricularia menziesii (section Pleiochasia: subgenus Polypompholyx). This study aimed to examine the micromorphology of U. menziesii flowers to assess traits that might be linked to its pollination strategy. • Methods Light microscopy, histochemistry and scanning electron microscopy were used. Nectar sugar composition was analysed using high-performance liquid chromatography. • Key Results The flowers of U. menziesii fulfil many criteria that characterize bird-pollinated flowers: red colour, a large, tough nectary spur that can withstand contact with a hard beak, lack of visual nectar guides and fragrance. Trichomes at the palate and throat may act as tactile signals. Spur nectary trichomes did not form clearly visible patches, but were more frequently distributed along vascular bundles, and were small and sessile. Each trichome comprised a single basal cell, a unicellular short pedestal cell (barrier cell) and a multicelled head. These trichomes were much smaller than those of the U. vulgaris allies. Hexose-dominated nectar was detected in flower spurs. Fructose and glucose were present in equal quantities (43 ± 3.6 and 42 ± 3.6 g L-1). Sucrose was only detected in one sample, essentially at the limit of detection for the method used. This type of nectar is common in flowers pollinated by passerine perching birds. • Conclusions The architecture of nectary trichomes in U. menziesii was similar to that of capitate trichomes of insect-pollinated species in this genus; thus, the most important specializations to bird pollination were flower colour (red), and both spur shape and size modification. Bird pollination is probably a recent innovation in the genus Utricularia, subgenus Polypompholyx, and is likely to have evolved from bee-pollinated ancestors.
Keywords: Australian bladderwort; Bird pollination; Carnivorous plant; Floral micro-morphology; Hplc; Lentibulariaceae; Nectar composition; Nectary structure; Ornithophily; Sect. pleiochasia; Spur; Trichomes